Effect of thickness reduction on the limit strain measurement for thermomechanical tensile tests - Lane,C; Shao,Z; Zheng,K; Lin,J (Manufacturing Review, 2018)
Sheet metal formability under hot stamping conditions can be evaluated by using a novel planar testing system in the Gleeble. However, the specimen designs with the central recess have not been standardised, and the thickness reduction was not applied to the dog-bone type of specimen for testing at the uniaxial straining state. In this paper, effect of thickness reduction of dog-bone specimens on limit strain measurement under hot stamping conditions is investigated, and two types of dog-bone specimens without and with central recess are presented. Thermomechanical uniaxial tensile tests were performed at various deformation temperatures and strain rates, ranging from 370 – 510°C and 0.01 – 1/s, respectively, by using the developed biaxial testing system in the Gleeble. The distributions of temperature and axial strain along gauge region of the two types of specimen were measured and compared. The specimen with consistent thickness had a better uniformity of temperature and strain distributions compared to that with thickenss reduction. Forming limits for both types of specimen were also determined using the section-based international standard method. It is found that the calculation of forming limits by using specimen with thickness reduction was highly dependent on the selection of the deformation stage.